STUDI TAFSIR AL-QUR’AN SURAT AL-ALAQ 1-5 SEBAGAI SUMBER PENGETAHUAN DALAM PENDIDIKAN ISLAM - Mufaizah Mufaizah; Vina Maulidatul Lailiyah (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This Tafsir of the Quran is intended to explain the meanings of the terms found in the Quran with a more comprehensive approach, particularly regarding the parts of verses that may be confusing or unclear. Surah Al-'Alaq, specifically verses 1-5. The methodology used in this research involves the collection and analysis of texts from the Quran. This research also compares previous research findings with verses in the Quran that are related to the origins of knowledge. The study's findings indicate that many verses in the Quran relate to references used in Islamic education. The main objective of this research is to identify knowledge used in the context of Islamic education by analyzing Surah Al-'Alaq verses 1-5.This discussion seeks to understand how the positive contributions of the Qur'an can deepen our knowledge of the universe and various aspects of life. The clear guidelines in reading outlined in Surah Al-'Alaq become the key to achieving success and serve as a foundation of knowledge.